STRUCTURAL ANALYSIS OF FOURTH CLASS MECHANISMS WITH THREE COMPLEX LINKS - KOSHEL, SERGEY; KOSHEL, GANNA; ZALYUBOVSKYI, MARK; KOSHEL, OLEXANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A structural study of a complex planar mechanism of the fourth class with one driving link and a moving closed loop was performed. The contour has the form of a quadrangle, which is formed by three links that have plane-parallel movement and one link that rotates around a fixed axis. The circuit is formed by four links: three connecting rods, two of which are complex links and are located opposite each other, and one rocker, which takes part in the formation of three kinematic pairs. Structurally, the set of six links and nine kinematic pairs, which is the basis of a complex mechanism, belongs to the group of links of the fourth class and the third order. We have developed possible variants of structural groups of links of the fourth class of the third order with a closed circuit, in which the nature of kinematic pairs and their location were taken into account. For various variants of structural groups of links, we obtained structural formulas of structures of mechanisms of the fourth class. We used the method of structural change of the actual leading link of the mechanism with another conditionally possible one. The obtained results of the study allow us to determine the sequence of further studies of the fourth-class mechanism with one structural group of higher-class links in the form of a second-class mechanism with three sequentially connected structural groups of the corresponding class.
Keywords: structural analysis; complex mechanism; structural group of links; higher class mechanism